FURTHER OBSERVATIONS ON THE RELEVANCE OF SEROLOGIC RECAPITULATIONS OF HUMAN INFECTION WITH INFLUENZA VIRUSES - Davenport, F. M. (The Rockefeller University Press, 1964)
By use of a photometric method which objectively distinguishes between homologous and heterologous antibody reactions, the age distribution of specifically reacting swine and Asian antibodies present in sera of persons not recently exposed to either virus was established. The findings support the thesis that the unique distribution by age of swine and Asian antibodies recognizes two past periods of prevalence of swine and Asian-like viruses, respectively. The findings apparently refute the conclusion that the existence of age-specific Asian and swine antibody patterns is primarily attributable to the undirected or passive accumulation of experience with Asian or swine antigens present as minor antigenic components in most strains of influenza A.